Giant Retinal Tear Management at Referral Eye Hospital - Purnama, Mia; Iskandar, Erwin; Virgana, Rova; Ihsan, Grimaldi; Sovani, Iwan; Kartasasmita, Arief (International Journal of Retina, 2018)
Introduction: to report the characteristics, management and outcome in giant retinal tear (GRT) associated retinal detachment patients at Cicendo Eye Hospital Methods: this retrospective study was performed on medical records who had undergone retinal detachment surgery between January 2014 and March 2017. Age, sex, etiologies, size of GRT, quadrant involvement, lens status, proliferative vitreo-retinopathy (PVR), managements and outcomes were evaluated in association with giant retinal tears Result: Twenty-six patients (23 males, 3 females) age between 11-59 years with follow up from 2 months to 18 months were enrolled in this study. Twenty-five eyes have retinal detachment with macular involvement and 11 patients had high myopia. Majority of patients had 90Â° of GRTs. Most retinal tears were located at temporal quadrant (73%). Nineteen patients had undergone pars plana vitrectomy (PPV) and 7 patients had combined PPV with encircling buckle. Fifteen patients had used heavy liquid, 24 patients had silicon oil and 2 had gas tamponade. Intraoperative complications included lens trauma, retinal slippage and choroidal detached were found in 1 eye respectively. Fourteen eyes had recurrent retinal detachment. At the last follow up, 14 patients had anatomically attached retina. Twelve patients had total retinal detachment and marked PVR. Five fellow eyes were treated with prophylactic laser. Visual acuity improved in 11 eyes. Conclusion: Giant retinal tears were more common in patients with high myopia. Management of GRT currently with PPV and PPV combined with encircling buckle. The success rate of anatomy and visual acuity was less than other previous studies